Hubungan status sosial ekonomi dengan status anemia pada ibu hamil trimester I dan Trimester III di Puskesmas Kediri - Hardaniyati; Dian Soekmawaty Riezqy Ariendha; Irni Setyawati (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2024)
Introduction: Iron is an essential microelement for the body, especially needed in the formation of blood cells. Pregnancy anemia causes blood-related changes resulting in a decrease in Hb levels in the blood. Data obtained from the Kediri Community Health Center, West Lombok Regency in 2021, the prevalence of anemia in mothers Pregnancy rate of 28.55% is the second highest in West Lombok Regency. Objective: To determine the relationship between economic status and anemia status in pregnant women at Kediri health centers. Methods:Type of analytical survey research with a Cross Sectional study approach. The sample for this research was 63 respondents with a Purposive Sampling technique, the inclusion criteria were pregnant women who were willing, able to read and write, and without complications. Data collection is carried out using an Hb meter that has been tested and calibrated by an expert at the time of purchase. The questionnaire sheet has also been tested for validity and reliability. Analysis uses the chi-square statistical test Results: Characteristics of respondents based on age 20-35 were 39 respondents 62.0%, working as housewives 26 respondents (41.2%), low economic status 44 respondents (65.0%), chi-square results showed that the square obtained p-value was 0.023, p value < 0.05.Conclusion: There is a relationship between economic status and anemia status in pregnant women at the Kediri health center